Manajemen Pembiayaan Pendidikan Berbasis Digital Pada Pondok Pesantren di Klaten - Priyanta, Priyanta; Hidayati, Dian; Sudarsono, Bambang; Hasanah, Enung (Manajemen Pendidikan, 2024)
Implementation of technology-based education financial management in Islamic boarding schools in Indonesia can provide an effective solution for managing funds. however, the lack of education financial management is reflected in the use of applications that are not yet optimal, which results in the data collection, processing and data search processes being less efficient. this research aims not only to determine the capacity of Islamic boarding schools in Klaten in facing changes in digital-based education financial management, but also to describe and analyze digital-based education financial management at Islamic boarding schools in Klaten. the research method used is descriptive qualitative research. the results of this research show that Islamic boarding schools in Klaten have implemented digital-based education financial management with the syahriah application. the process involves planning, organizing, implementing, and monitoring. the benefits of digital-based payments provide convenience for guardians of santri, including payment of tuition fees, top-ups, and monitoring of arrears. for treasurers/staff, using this application helps in checking, minimizing errors, providing payment notifications, and increasing the efficiency of financial reports. even though there are obstacles such as not understanding its use, outreach to student guardians and a quick response from BSI is a solution to these technical obstacles. the conclusion from this research is that the Islamic boarding school in Klaten has succeeded in implementing digital-based financial management providing significant benefits for student guardians and the treasurer/staff. even though there are technical obstacles, the solution presented is quite suitable.